Pengolahan Kompos Dari Rumput Naga (Potamogeton sp) Menggunakan Tiga Macam Isolat Trikoderma Sebagai Dekomposer - Rahman, Fathur; Marsuni, Yusriadi; Khamidah, Noor (Agroekotek View, 2023)
Dragon grass (Potamogeton sp) is an aquatic plant found in the waters. In irrigation waters the presence of dragon grass is very disturbing to the irrigation manager because it reduces the water discharge along the irrigation route. This plant contains N = 3.36%, P = 0.41%, and K = 3.10% so that it has the potential to be processed into compost. Dragon grass can be used as compost using a decomposer, one of which is Trichoderma or commonly known as Trikokompost. This study aims to determine the quality of compost from dragon grass (Potamogeton sp) using three kinds of trichoderma isolates as decomposers and to determine which types of trichoderma are effective as decomposers. This research was carried out in the Greenhouse of the Department of Agroecotechnology and the Laboratory of Soil Physics and Chemistry, Faculty of Agriculture, Lambung Mangkurat University Banjarbaru from September - November 2020. The study used a completely randomized design (CRD). namely the administration of trichoderma decomposers consisting of 5 treatments which were repeated 4 times, so that 20 experimental units were obtained. Observation parameters in the study were C/N ratio, pH, temperature, humidity, macro and micro nutrients. The results showed that the type of trichoderma which is effective as a decomposer in making compost from dragon grass is Trichoderma harzianum. All parameters of macro and micro nutrients in dragon grass compost (Potamogeton sp) have met the criteria of SNI 19-7030-2004.